أسماء التفضيل في القرآن الكريم والحديث النبوي الشريف - دارسة دلالية The names of preference in the Quran and Hadith - Semantic Study - Zeki, Akram M.; Abdulghafor, Rawad Abdulkhaleq Abdulmolla (2018)
This study aims to review on the semantic studies in the Quran and Hadith.This subject has been chosen because of its importance in the detection of multiple implications of the name of the preference in the Quran and Hadith. Furthermore; this research aims to study the names of preference in the Quran and Hadith. The problem statements of this research we can be express in three main parts. The first part concerns the preference names positive and negative. The second part concerns the prevent exchange of formula: I do and the feminization of the formula I do assemble. The third part concerns the significance of this formula to participate applied on Quran and Hadith with a statement of their appearance. In this research we used the basics in mathematics at the words and meanings of the Quran and Hadith. The importance of this research lies in that it shares a statement preference name in the methods at all "it is the Quran and Hadith". Moreover; this study gives a descriptive semantic of human effort. We ask Allah the success in this life and in the hereafter.